Perbandingan Efektifitas Aktivator Mol Air Nasi Basi Dan Mol Ragi Dalam Pembuatan Kompos Dari Sampah Organik Dengan Metode Takakura - La Ode Tasrun; Ririn Teguh Ardiansyah; Bromo Kusuma Achmad (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Abtract Organic waste is an environmental pollution problem that requires the most dominant treatment. Due to the lack of organic waste treatment to change its shape into something beneficial, organic wastes processing becomes compost by adding local microorganisms to the takakura method.The problem with the study is whether the water distribution of stale rice and yeast moles in a dose of 30 ml [10 ml], 40 ml [12 ml] and 50 ml (each of the same doses) is effective in organic garbage treatment to make up the purpose of the study to know the dosage of stale rice and yeat-grown yeast lags in organic waste processing become compos. The design of this research is a preexperimental one by giving two different activators at organic litter with mol actuators of stale rice and yeast mole in the organic garbage treatment into composing. Using univariable data analysis. Research indicates that the yeast mole activation by a dose of 30 ml [12 ml], 40 ml. And 50 ml [5 ml] has a faster and more efficient time for producing organic waste than the actual dose of stale rice mole release. It was determined that the more microorganisms contained in the material of mole activation that was used, the faster it would take to become organic compost. It is recommended to the public to make good use of organic garbage by using the natural ingredients of yeast and rice-based local microorganisms in the pumping process.